UJI DAYA TERIMA DAN KOMPOSISI GIZI BOLU KUKUS LOW GLYCEMIX INDEX UNTUK PENDERITA DIABETES MELITUS - Susyani; Rifada Elzanabilah; Yuli Hartati (Media Gizi Pangan, 2023)
Diabetes mellitus is a disease with insulin secretion abnormalities characterized by hyperglycemia, this disease is relatively long, so insulin cannot be used effectively. DM disease characterized by increased blood glucose in fasting blood glucose > 126 mg/dl and random blood glucose > 200 mg/dl. Research objectives: To create a low glycemic index steamed sponge cake formulation to reduce blood glucose levels in DM sufferers. Methods: This research is an experimental study. This research using a non-factorial completely randomized design (CRD) with 4 treatments. The organoleptic test research subjects were 25 panelists. Research results: Based on the results of research on organoleptic tests (taste, texture, aroma and color) it shows that the preferred low glycemic index of steamed sponge cake is F3. Based on the ANOVA test, it can be seen that the significant value for color is 0.105 and taste is 0.245 this shows that the aspects that most panelists like about the low glycemic index steamed sponge cake are the color and taste aspects. This formula contains 283.97 kcal energy (per 100 grams), 11.58% protein, 14.69% fat, 26.36% carbohydrates, 45.28% water content, 2.08% ash content, 8 dietary fiber, 12%, and anthocyanins 18.71% Conclusion: Based on the research results, it can be concluded that the addition of purple sweet potato flour and tempeh flour to low glycemic index steamed sponge cake can be used as an alternative snack that is high in fiber and low in glycemic index for DM sufferers.